A numerical experiment of cold front induced circulation in Wax Lake Delta: evaluation of forcing factors - Feizabadi, Sajjad; Li, Chunyan; Hiatt, Matthew (Frontiers in Marine Science, 2023)
The effects of passing atmospheric cold fronts with different orientations and moving directions on the hydrodynamics of the Wax Lake Delta (WLD) were analyzed by considering the influence of river discharge, cold front moving direction, wind magnitude, and Coriolis effect. The study employs numerical simulations using the Delft-3D model and an analytical model to explore water volume transport, water level variations, water circulation, and particle trajectories during nine cold front events. Results indicate that cold fronts cause a decrease in the average contribution of the water transport through western channels and an increase of that in central and eastern channels. A westerly cold front with an average wind speed of 12 m/s can increase water transport through eastern channels by about 35%. During the passage of a cold front, the intertidal islands between the main channels and East Bay experience the largest fluctuations in subtidal water levels, which can be attributed to the influence of local wind stress. For example, a westerly cold front can result in a water level variation of approximately 0.45 m over some of the intertidal Islands and 0.65 m in the East Bay. Results also show that the subtidal water circulation in the WLD is correlated with the Wax Lake Outlet (WLO) discharge and wind magnitude. The findings illustrate that when WLO discharge is low, the impact of cold fronts is more pronounced, and cold fronts from the west have a greater impact compared to those from the northwest and north. This study identifies the significance of WLO discharge and Coriolis force by the trajectories of particles in the water column. The results of the simulations indicate that under low WLO discharge (less than 2000 m3/s), the majority of particles are found to exit through Campground Pass instead of Gadwall because of the dominance of Coriolis force. To summarize, this study assesses the impact of cold fronts on the hydrodynamics of the Wax Lake Delta, underscoring the contributions of multiple factors, including the cold front moving direction, river discharge, wind strength, and Coriolis force.